2012
DOI: 10.1007/s11661-012-1201-x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Twin Screw Rheo-Extrusion of an AZ91D Magnesium Alloy

Abstract: The twin screw rheo-extrusion (TSRE) is designed to take advantage of the nondendritc microstructure and thixotropic characterization of semisolid-metal slurries and produce simple metal profiles directly from melts. The extrusion equipment consists of a rotor-stator high shear slurry maker, a twin screw extruder, and a die assembly. The process is continuous and has a potential for significantly saving energy, manufacturing cost, and enhancing efficiency. The present investigation was carried out to study the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…in groups 1 and 2, respectively. As mentioned above, Xia and coworkers [19] have demonstrated that 0.5-0.7 solid fractions is a suitable range for rheo-extrusion. So alloy 6 can be the best candidate for rheo-extrusion at F s = 0.6.…”
Section: Thermodynamic Analysis Of Alloysmentioning
confidence: 86%
See 2 more Smart Citations
“…in groups 1 and 2, respectively. As mentioned above, Xia and coworkers [19] have demonstrated that 0.5-0.7 solid fractions is a suitable range for rheo-extrusion. So alloy 6 can be the best candidate for rheo-extrusion at F s = 0.6.…”
Section: Thermodynamic Analysis Of Alloysmentioning
confidence: 86%
“…[12][13][14][15][16][17]. Fan et al [18,19] have developed a new SSM processing technology named twin-screw rheoextrusion. Semi-solid rheo-extrusion is a new extrusion process that has several advantages such as low extrusion force, high fluidity of materials, and low friction force between the die and the materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…is required to enhance the nucleation rate and restrict the growth of primary particles and consequently lead to the formation of slurries with uniform and refined microstructure [9]. Among above fields, while the twin screw shearing [10], gas bubble stirring [11,12] and ultra-sonic vibration [13] are able to produce fine and spherical primary particles, they tend to introduce slags and oxidized films (in particular, Mg melt is highly active and prone to be oxidized [14]) into the melt, which would cause the premature fracture of alloy. On the other hand, electro-magnetic stirring, which would not cause oxidation and subsequent contamination of the melts, appears to be suitable to be used to prepare slurries of Mg alloys.…”
Section: Introductionmentioning
confidence: 99%
“…T. Campanella and M. Rappaz et al proposed a dendrite fragmentation criterion to study the grain refinement effect by electromagnetic stirring treatment, and proved this theory by experimental study on two kinds of Cu alloys [19]. In addition, previous researches were mainly toward Al alloys and Mg-Al based alloys [10,12,13,[20][21][22], while very little work has been carried out toward the Mg-RE based alloys.…”
Section: Introductionmentioning
confidence: 99%